Terrorism in the Modern World-System: Towards the Problem of Prospects for Interdisciplinary Research - A. A. Izgarskaya; N. E. Lukyanov (Дискурс)
Introduction. The variety of approaches and topics in the study of terrorism, as well as the obvious difference in axiological grounds for assessing terrorist activity, allows the authors to raise the question of an interdisciplinary study of this problem. The authors understand terrorism as an illegal political confrontation in the struggle for power with the use of violence in order to intimidate or physically eliminate the enemy.Methodology and sources. The methodological basis of the work is the world-system concept of I. Wallerstein. The authors reveal the advantages of the world-system approach by comparing it with the paradigm of political realism in the theory of international relations. They indicate the boundaries of the paradigm of political realism, which operates at the level of the concepts of “States” and “International Coalitions”, while the phenomenon of terrorism includes structures at the level of groups and organizations. The world-systems approach allows researchers to see terrorism as an anti-system movement generated by the contradictions in the development of the system itself, to distinguish between pro-system and anti-system terrorism, to analyze this phenomenon at all societal levels. One of the essential advantages of the world-systems approach is its ability to accumulate different approaches and related disciplines in order to describe the dynamics of modern societies. In their theoretical constructions, the authors rely on the typology of terrorist organizations by O. Lizardo and A. Bergesen, as well as on the concept of waves of terrorism by D. Rapport. The authors conduct a critical analysis of the typology of terrorism by O. Lizardo, A. Bergesen and note that this typology helps to see the structural source (core, semi-periphery, periphery) and the main structural goal of terrorist organizations, but leaves behind such a phenomenon as state terrorism.Results and discussion. The authors describe terrorism in its interrelation with processes in the world system at different societal levels. At the super-macro level, the world-systems conditions for the emergence of waves of terrorist activity are described, and the links between terrorism and the struggle to establish a global order are indicated. At the macro level (the level of political confrontation for the establishment of some form of order within the state), the authors investigate the differences between terrorism in “closed” and “open” societies. They note the connection between bursts of terrorist activity and the transition from a “closed” to an “open” state and vice versa. The authors consider the connection of terrorism with the processes of the peripheralization of societies as a meso-level phenomenon. Such terrorism, as a rule, is local and is inspired by the national liberation slogans of the societies of the internal periphery, the authors note that the struggle with the state here can go for both sovereignty and disputed territories. The authors refer to the meso-level the activities of terrorist organizations aimed at migrants who come from the outer periphery. The authors note that the subject of terrorism research at the micro level is, as a rule, the personality of the terrorist.Conclusion. The use of a world-systems approach to consider terrorism seems promising, and allows researchers to consider structural relations that are not available to other approaches. The authors express the hope that the interdisciplinary capabilities of the world-systems approach, its methodological potential woul be able to form a reliable basis for subsequent studies of terrorism as one of the means of illegitimate political violence in the modern world.